KONSEP MANAJEMEN DAKWAH M. QURAISH SHIHAB: KAJIAN PUSTAKA ATAS PRINSIP WASATHIYYAH, HUMANISME, DAN DAKWAH KONTEKSTUAL - Nuri Salsabila; Selfi Febrianti; Pingkan Dhea Prasasti; Indri Maulidiyah; Anang Sholikhudin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Da'wah as a fundamental obligation in Islam requires systematic management to effectively address the challenges of modern society. This study aims to examine the da'wah thought of M. Quraish Shihab and explore its relevance in the context of contemporary da'wah. This research employs a qualitative approach through library research, analyzing the works of M. Quraish Shihab alongside relevant supporting literature. The findings reveal that Quraish Shihab's da'wah thought is grounded in the principles of moderation (wasathiyyah), humanism, and contextual engagement, which the researcher reconstructs into a da'wah management framework encompassing planning, organizing, implementing, and evaluating. In a contemporary context, these principles can be applied through dialogical and inclusive approaches, as well as the use of digital media as a means of fostering sustainable social transformation. This study contributes a conceptual framework for adaptive da'wah practice rooted in moderate Islamic values to meet the needs of modern society.